The crystal structure of the Dess–Martin periodinane - Schröckeneder, Albert; Stichnoth, Desiree; Mayer, Peter; Trauner, Dirk (Beilstein Journal of Organic Chemistry, 2012)
We report the elusive X-ray structure of the Dess–Martin periodinane (DMP), a hypervalent iodine reagent popular amongst synthetic chemists. In the solid state, the highly crystalline compound forms an intricate coordination polymer held together by intermolecular halogen and hydrogen bonds.
Keywords: crystal structure; Dess–Martin periodinane; halogen bonds; hypervalent iodine; oxidant

(untitled) - Dess, D. B.; Martin, J. C. (J. Am. Chem. Soc., 1991)

(untitled) - Dess, D. B.; Martin, J. C. (J. Org. Chem., 1983)

(untitled) - Zhdankin, V. V. (J. Org. Chem., 2011)

(untitled) - Zhdankin, V. V.; Stang, P. J. (Chem. Rev., 2008)

(untitled) - Frigerio, M.; Santagostino, M.; Sputore, S. (J. Org. Chem., 1999)

(untitled) - Ireland, R. E.; Liu, L. (J. Org. Chem., 1993)

(untitled) - Gougoutas, J. Z.; Clardy, J. C. (J. Solid State Chem., 1972)

(untitled) - Stevenson, P. J.; Treacy, A. B.; Nieuwenhuyzen, M. (J. Chem. Soc., Perkin Trans. 2, 1997)

The Nature of the Chemical Bond - Pauling, L. (Cornell University Press, 1960)

(untitled) - Fusaro, L.; Luhmer, M.; Cerioni, G.; Mocci, F. (J. Org. Chem., 2009)

(untitled) - Bondi, A. (J. Phys. Chem., 1964)

(untitled) - Politzer, P.; Lane, P.; Concha, M. C.; Ma, Y.; Murray, J. S. (J. Mol. Model., 2007)

(untitled) - Stergioudis, G. A.; Kokkou, S. C.; Bozopoulos, A. P.; Rentzeperis, P. J. (Acta Crystallogr., Sect. C, 1984)

(untitled) - Alcock, N. W.; Harrison, W. D.; Howes, C. (J. Chem. Soc., Dalton Trans., 1984)

(untitled) - Ochiai, M.; Takaoka, Y.; Masaki, Y.; Nagao, Y.; Shiro, M. (J. Am. Chem. Soc., 1990)

(untitled) - Zhdankin, V. V.; Maydanovych, O.; Herschbach, J.; McDonald, R.; Tykwinski, R. R. (J. Am. Chem. Soc., 2002)

(untitled) - Richardson, R. D.; Zayed, J. M.; Altermann, S.; Smith, D.; Wirth, T. (Angew. Chem., Int. Ed., 2007)

(untitled) - Miller, A. K.; Hughes, C. C.; Kennedy-Smith, J. J.; Gradl, S. N.; Trauner, D. (J. Am. Chem. Soc., 2006)

(untitled) - Metrangolo, P.; Meyer, F.; Pilati, T.; Resnati, G.; Terraneo, G. (Angew. Chem., Int. Ed., 2008)

(untitled) - Etter, M. C.; MacDonald, J. C.; Bernstein, J. (Acta Crystallogr., Sect. B, 1990)